Effectiveness of tocilizumab with and without synthetic disease-modifying antirheumatic drugs in rheumatoid arthritis: results from a European collaborative study - Gabay, Cem; Riek, Myriam; Hetland, Merete Lund; Hauge, Ellen-Margrethe; Pavelka, Karel; Tomšič, Matija; Canhao, Helena; Chatzidionysiou, Katerina; Lukina, Galina; Nordström, Dan C; Lie, Elisabeth; Ancuta, Ioan; et al. (Annals of the rheumatic diseases, 2016)
OBJECTIVES: To examine the effectiveness of tocilizumab (TCZ) with and without synthetic disease-modifying antirheumatic drugs (sDMARDs) in a large observational study. METHODS: Patients with rheumatoid arthritis treated with TCZ who had a baseline visit and information on concomitant sDMARDs were included. According to baseline data, patients were considered as taking TCZ as monotherapy or combination with sDMARDs. Main study outcomes were the change of Clinical Disease Activity Index (CDAI) and TCZ retention. The prescription of TCZ as monotherapy was analysed using logistic regression. CDAI change was analysed with a mixed-effects model for longitudinal data. TCZ retention was analysed with a stratified extended Cox model. RESULTS: Multiple-adjusted analysis suggests that prescription of TCZ as monotherapy varied according to age, corticosteroid use, country of the registry and year of treatment initiation. The change of disease activity assessed by CDAI as well as the likelihood to be in remission were not significantly different whether TCZ was used as monotherapy or in combination with sDMARDs in a covariate-adjusted analysis. Estimates for unadjusted median TCZ retention were 2.3 years (95% CI 1.8 to 2.7) for monotherapy and 3.7 years (lower 95% CI limit 3.1, upper limit not estimable) for combination therapies. In a covariate-adjusted analysis, TCZ retention was also reduced when used as monotherapy, with an increasing difference between mono and combination therapy over time after 1.5 years (p=0.002). CONCLUSIONS: TCZ with or without concomitant sDMARDs resulted in comparable clinical response as assessed by CDAI change, but TCZ retention was shorter under monotherapy of TCZ.
Keywords: Humans; lidé středního věku; Arthritis, Rheumatoid; antirevmatika; Treatment; Female; výsledek terapie; lidé; humanizované monoklonální protilátky; Europe; DMARDs (synthetic); revmatoidní artritida; Antibodies, Monoclonal, Humanized; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; Treatment Outcome; Severity of Illness Index; Rheumatoid Arthritis; DMARDs (biologic); mužské pohlaví; kombinovaná farmakoterapie; Antirheumatic Agents; Evropa; Drug Therapy, Combination